Host macrocyclic acylcarnitines mediate symbiotic interactions between frogs and their skin microbiome - Brunetti, Andrés E.; Lyra, Mariana L.; Bauermeister, Anelize; Bunk, Boyke; Boedeker, Christian; Müsken, Mathias; Neto, Fausto Carnevale; Mendonça, Jacqueline Nakau; Caraballo-Rodríguez, Andrés Mauricio; Melo, Weilan G.P.; Pupo, Mônica T.; Haddad, Célio F.B. [UNESP]; et al. (Elsevier, 2023)
The host-microbiome associations occurring on the skin of vertebrates significantly influence hosts’ health. However, the factors mediating their interactions remain largely unknown. Herein, we used integrated technical and ecological frameworks to investigate the skin metabolites sustaining a beneficial symbiosis between tree frogs and bacteria. We characterize macrocyclic acylcarnitines as the major metabolites secreted by the frogs’ skin and trace their origin to an enzymatic unbalance of carnitine palmitoyltransferases. We found that these compounds colocalize with bacteria on the skin surface and are mostly represented by members of the Pseudomonas community. We showed that Pseudomonas sp. MPFS isolated from frogs’ skin can exploit acylcarnitines as its sole carbon and nitrogen source, and this metabolic capability is widespread in Pseudomonas. We summarize frogs’ multiple mechanisms to filter environmental bacteria and highlight that acylcarnitines likely evolved for another function but were co-opted to provide nutritional benefits to the symbionts.
Keywords: Biological sciences; Metabolomics; Microbial metabolism; Microbiology; Omics